PENYULUHAN PENGGUNAAN TANAMAN OBAT KELUARGA (TOGA) UNTUK PENGOBATAN DI DESA LAJUT - Lalu Ardian Hadi; Fiona Erlita Meiyani; Minzorus Sunan; Immy Suci Rohyani (Jurnal Abdi Insani, 2022)
Indonesia has many varieties of plants that are blessed as medicine. Availability of these medicinal plants is utilized by the people for traditional medicine to meet their treatment. Family Medicinal Plant (TOGA) is a medicinal plant grown in the yard of a family-run house as an independent effort in medicine. Lajut Village in utilizing TOGA as medicine is still lacking, so it is important to socialize about TOGA. Socialization will improve people's ability to manage TOGA into products that are ready for consumption. The method used is by talking about the types of TOGA and their benefits, how to harvest TOGA, post-harvest treatment of TOGA, procedures for making TOGA symplisia, and discussions on how to process TOGA that is ready for consumption. The results of observations made with the head of Kandong and Tempas hamlet obtained as many as 24 types of TOGA, 8 types of which were presented in counseling in the hall of the Lajut village office. The evaluation of the socialization of people in Lajut village shows an increase in public knowledge about how to use TOGA for family medicine alternatives. Knowledge of participants increased from 54.8% to 72% obtained from the results of pre-test and post-test scores. The education level of the participants was dominated by high school (48%), bachelor (36%), junior high school (8%), and elementary school (8%). The implementation of this socialization can increase the knowledge of the people of Lajut village regarding the use of TOGA for preventive efforts, promotive efforts, and curative efforts.